Deciphering nasal septum deviation: Computed tomography insights into age and gender trends for optimized clinical care - Shalini Sharma,; Garima Sehgal,; Noor Us Saba,; Jyoti Chopra,; Gopal Tiwari, (Asian Journal of Medical Sciences, 2024)
Background: Deviation of the nasal septum (DNS) is defined as any deviation of the septum from the midline and is one of the most common variations of the sinonasal anatomy. Aims and Objectives: The purpose of this study was to observe the prevalence of DNS and its relation with age, gender, and sidedness. Materials and Methods: Sinonasal computed tomographic images of 100 subjects obtained from the Department of Radiodiagnosis, King George’s Medical University, Lucknow, UP, in the period August 2013–July 2014 were analyzed to determine the prevalence of DNS and its relation with age, gender, and sidedness. Results: Of a total of 100 subjects, normal midline nasal septum was seen in 27 subjects whereas 73 subjects (73%) displayed a deviation in its position. The prevalence of nasal septal deviation (NSD) was significantly higher in females (84.21%) as compared to males (66.13%) (P=0.048). We also compared the prevalence of NSD in different age groups and found it to be higher in subjects aged >46 years (83.33%) as compared to other age groups but this difference was not found to be statistically significant (P=0.619). Conclusion: Nasal septu the septum toward the right. No correlation between age intervals and prevalence of DNS was found.